2016
DOI: 10.1039/c6ra09528c
|View full text |Cite
|
Sign up to set email alerts
|

High catalytic activity of Co3O4 nanoparticles encapsulated in a graphene supported carbon matrix for oxygen reduction reaction

Abstract: A simple method has been adopted for the synthesis of Co3O4 nanoparticles encapsulated in graphene supported carbon matrix, which could exhibit higher catalytic performance for oxygen reduction reaction than the commercial Pt/C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Accordingly, the electron transfer number, n, was close 3.8, which is a value rather close to 4 of typical Pt [52]. Our methodology was consistent with what was reported in the literature [42,55]. According to a prior study, the Co3O4 catalyzed the ORR in a 2.9 to 3.4-electron route [56].…”
Section: Characterization Of Co3o4@pt/gn For Orr Activitiessupporting
confidence: 90%
“…Accordingly, the electron transfer number, n, was close 3.8, which is a value rather close to 4 of typical Pt [52]. Our methodology was consistent with what was reported in the literature [42,55]. According to a prior study, the Co3O4 catalyzed the ORR in a 2.9 to 3.4-electron route [56].…”
Section: Characterization Of Co3o4@pt/gn For Orr Activitiessupporting
confidence: 90%
“…Cobalt oxides based materials having superb structural and compositional semblance with enriched electroactive sites are considered as feasible candidate for ORR [ 16 , 17 , 18 ]. Hybridizing two metal oxides has been considered as potential class of alternatives that can significantly boost the electrochemical performance towards ORR [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was robust to allow the replacement of Zn anode and electrolyte periodically, which could be an ideal cathode electrocatalyst for EVs. Xie et al 117 reported a catalyst consisting of Co 3 O 4 nanoparticles encapsulated in a graphene supported carbon matrix (Co 3 O 4 @C/graphene) with higher electrocatalytic activity and better stability compared with commercial 20 wt % Pt/C. They proved the synergistic coupling between Co 3 O 4 and nitrogen-doped graphene.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%